Australian police detainees who use anabolic-androgenic steroids (AAS) and their involvement in violent crimes compared to detainees using substances other than AAS. (February 2023) - van de Ven, Katinka; Zahnow, Renee; Livingston, Michael
Highlights: Being charged with a violent crime does not seem to be a unique feature of detainees who use anabolic-androgenic steroids (AAS), with the prevalence of violent crime among detainees no different to those who use other substances. The link between violence and AAS use is complex, with poly-drug use and risk-taking behaviours more broadly seeming to play an important role. Caution needs to be applied when depicting AAS as a direct precursor to violence. Programs are needed that support violent offenders to overcome their drug dependence and their criminal offending. Abstract: Introduction: Although anabolic-androgenic steroid (AAS) use is associated with an increased risk of violent behaviour, this relationship is complex. Many methodological issues also exist with current studies and most focus on community or prison settings, targeting people who use AAS only. This will be the first Australian study to compare police detainees who at the time of arrest report the use of AAS with those who report using other substances in the past 12 months; focussing on demographic characteristics, most serious charged offences and presence of poly-drug use. Methods: Data is drawn from the Drug Use Monitoring in Australia (DUMA) program, which collects data around drug use and criminal justice information from police detainees across Australia. Data was requested for 2017-2021. Our sample included 10, 105 offenders who reported substance use, including 312 who had used AAS. Results: We found that detainees who had used AAS in the 12 months before their offence were charged with violent crimes (40.5%) at a similar rate to those who used substances other than AAS (36.5%). We found high rates of other substance use amongst AAS-using detainees, particularly alcohol and stimulants. Discussion and conclusions: Committing violent offences does not seem to be a unique feature of individuals using AAS, with the prevalence of violent crime among detainees no different to those who use other substances. It however did form the most serious offence of the majority of detainees who used AAS. Drug programs for violent offenders to overcome their drug dependence and criminal offending are however absent.